Reducing Radiation Dose in Emergency CT Scans While Maintaining Equal Image Quality: Just a Promise or Reality for Severely Injured Patients? - Grupp, Ulrich; Schäfer, Max-Ludwig; Meyer, Henning; Lembcke, Alexander; Pöllinger, Alexander; Wieners, Gero; Renz, Diane; Schwabe, Philipp; Streitparth, Florian (Emergency Medicine International, 2013)
Objective. This study aims to assess the impact of adaptive statistical iterative reconstruction (ASIR) on CT imaging quality, diagnostic interpretability, and radiation dose reduction for a proven CT acquisition protocol for total body trauma. Methods. 18 patients with multiple trauma (ISS≥16) were examined either with a routine protocol (n=6), 30% (n=6), or 40% (n=6) of iterative reconstruction (IR) modification in the raw data domain of the routine protocol (140 kV, collimation: 40, noise index: 15). Study groups were matched by scan range and maximal abdominal diameter. Image noise was quantitatively measured. Image contrast, image noise, and overall interpretability were evaluated by two experienced and blinded readers. The amount of radiation dose reductions was evaluated. Results. No statistically significant differences between routine and IR protocols regarding image noise, contrast, and interpretability were present. Mean effective dose for the routine protocol was 25.3±2.9 mSv, 19.7±5.8 mSv for the IR 30, and 17.5±4.2 mSv for the IR 40 protocol, that is, 22.1% effective dose reduction for IR 30 (P=0.093) and 30.8% effective dose reduction for IR 40 (P=0.0203). Conclusions. IR does not reduce study interpretability in total body trauma protocols while providing a significant reduction in effective radiation dose.